Bortezomib Sustains T Cell Function by Inducing miR-155-Mediated Downregulation of SOCS1 and SHIP1 - Renrick, Ariana N.; Thounaojam, Menaka C.; de Aquino, Maria Teresa P.; Chaudhuri, Evan; Pandhare, Jui; Dash, Chandravanu; Shanker, Anil (Frontiers in Immunology, 2021)
Suppressive mechanisms operating within T cells are linked to immune dysfunction in the tumor microenvironment. We have previously reported in adoptive T cell immunotherapy models that tumor-bearing mice treated with a regimen of proteasome inhibitor, bortezomib - a dipeptidyl boronate, show increased antitumor lymphocyte effector function and tumor-free survival. Here, we identify a mechanism for the improved antitumor CD8+ T cell function following bortezomib treatment. Intravenous administration of bortezomib at a low dose (1 mg/kg body weight) in wild-type or tumor-bearing mice altered the expression of a number of miRNAs in CD8+ T cells. Specifically, the effect of bortezomib was prominent on miR-155 - a key cellular miRNA involved in T cell function. Importantly, bortezomib–induced upregulation of miR-155 was associated with the downregulation of its targets, the suppressor of cytokine signaling 1 (SOCS1) and inositol polyphosphate-5-phosphatase (SHIP1). Genetic and biochemical analysis confirmed a functional link between miR-155 and these targets. Moreover, activated CD8+ T cells treated with bortezomib exhibited a significant reduction in programmed cell death-1 (PD-1) expressing SHIP1+ subset of cells. These data underscore a mechanism of action by which bortezomib induces miR-155–dependent downregulation of SOCS1 and SHIP1 negative regulatory proteins, leading to a suppressed PD-1–mediated T cell exhaustion. Collectively, data provide novel molecular insights into bortezomib–mediated lymphocyte–stimulatory effects that could overcome immunosuppressive actions of tumor on antitumor T cell functions. The findings support the approach that bortezomib combined with other immunotherapies would lead to improved therapeutic outcomes by overcoming T cell exhaustion in the tumor microenvironment.